KOMPARASI HASIL BELAJAR ANTARA SISWA YANG BEKERJA DENGAN YANG TIDAK BEKERJA SMKN 3 PONTIANAK - Permadi, Rangga; Ulfah, Maria; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this study was to determine how the results of introductory accounting learning subjects between students who work with students who do not work in class X of SMK Negeri 3 Pontianak. The research method is Expost Facto with the form of causal-comparative research. The source of this research data is students of class X accounting with the number of research subjects as many as 18 students who work and 18 students who do not work. The research collected data from midterm repetition of introductory accounting subjects for class X in academic year 2017/2018. The results showed that there was no significant difference in learning outcomes between students who worked with students who did not work in class X Accounting which was shown at the significance of the calculation of 0.596> Î± 0.05, Std Error Difference of 5.65062, and the variant Levene's Test For Equality Of Variances 0.994> Î± 0.05. From the data analysis that the hypothesis: there is a significant difference in learning outcomes between students who work with students who do not work is not accepted or Ho = 0 is accepted Ha â‰  0 is rejected which means that there is no significant difference in learning outcomes between students who work with students who do not work on Introduction to Accounting subjects. This means that Working does not deter learning success.Keywords: Introduction to Accounting, Learning Outcomes, and Students work and not work